TIME BUDGET PRESSURE ON THE RELATION BETWEEN PUBLIC TRUST AND AUDITOR INDEPENDENCE IN PUBLIC ACCOUNTING FIRM - Andi Ina Yustina; Imas Nur Islami (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
The number of cases that occur involving the auditor or accountant raises a big question mark in the community about the responsibility of the auditor. The literature related to auditor behavior has been discussed by researchers to look for several possible causes of fraud. Although based on the AICPA rules that an auditor must have integrity, independence, serve the public, and have a level of trust in the public but the demands of work as an auditor make it very vulnerable to stress. The purpose of this study is to examine the role of time budget pressures in weakening public trust and auditor independence. This research will use quantitative methods with data collection methods by the survey. A total of 87 questionnaires collected from auditors working at Big 4 and Non-Big 4. Public Accountant Firms. The test was conducted using SEM-PLS. The results of this study indicate that time budget pressure is not influence to auditor independence. However, public trust is proven to have a relationship with auditor independence.